The Inter-American System and Women's Rights - O'Connell, Ciara (Springer Press Singapore, 2018)
The Inter-American System of Human Rights has proven itself to be a forum for the advancement of women’s rights. From developing the first women’s rights treaty specifically designed to address violence against women, to issuing reparations that require states to prevent gender discrimination, the Inter-American System has increasingly led the way in promoting a women’s rights lens to examine international human rights law. While its efforts to uncover the causes of women’s rights violations may fall short at times, the jurisprudence emerging from the Inter-American System of Human Rights provides lessons on how, and how not to, develop women’s rights litigation. This chapter provides an overview of the regional system’s women’s rights convention (the Convention of Belém do Pará), highlights notable advancements in developing women’s rights in the Inter-American region, and discusses several landmark women’s rights cases recently decided by the Inter-American Court of Human Rights. It concludes by looking forward to the Inter-American System’s upcoming challenges and opportunities for advancing women’s rights in the region.
International Human Rights of Women
Keywords: Inter-American Human Rights system; Regional human rights systems; Women's rights litigation; Criminology, Equality and Human Rights law, feminist theory; Gender Equality; Human Rights